A sociocultural study on solar photovoltaic energy system in India: Stratification and policy implication - Padmanathan K.; Govindarajan U.; Ramachandaramurthy V.K.; Rajagopalan A.; Pachaivannan N.; Sowmmiya U.; Padmanaban S.; Holm-Nielsen J.B.; Xavier S.; Periasamy S.K. (Elsevier Ltd, 2023)
Energy policy; Natural resources; Pollution control; Public policy; Solar concentrators; Solar energy; Statistical mechanics; Surveys; Biplot interpretation; Dendrograms; Socio-technical regimes; Solar photovoltaics; Structural equation modelling; Solar power generation